Intravenous Pantoprazole as an Adjuvant Therapy following Successful Endoscopic Treatment for Peptic Ulcer Bleeding - Jun Wang; Kehu Yang; Bin Ma; Jinhui Tian; Yali Liu; Zhenggang Bai; Lei Jiang; Shaoliang Sun; Jun Li; Ruifeng Liu; Xiangyong Hao; Xiaodong He (Canadian Journal of Gastroenterology)
BACKGROUND: Several studies have suggested that proton pump inhibitors are efficacious in preventing rebleeding when administered immediately after endoscopic treatments. However, there are limited clinical outcome data on the use of intravenous pantoprazole.